Settlement and land use on the periphery : the Bouros-Kastri Peninsula, Southern Euboia - Wickens, Jere Mark, 1950- (Archaeopress Publishing Ltd, 2018)
This survey by the Southern Euboea Exploration Project provides a wealth of intriguing information about fluctuations in long-term use and habitation in the Bouros-Kastri peninsula at the south-eastern tip of the Greek island of Euboia, and how the peninsula's use was connected to that of the main urban centre at Karystos.